The prevalence of major depression and generalized anxiety disorder in patients with multiple sclerosis in Saudi Arabia: a cross-sectional multicentered study - Alswat, Anas M.; Altirkistani, Bsaim A.; Alserihi, Anas R.; Baeshen, Osama K.; Alrushid, Eythar S.; Alkhudair, Joud; Aldbas, Abdulaziz A.; Wadaan, Osama M.; Alsaleh, Ahmad; Al Malik, Yaser M.; Abulaban, Ahmad A.; Makkawi, Seraj (Frontiers in Psychiatry, 2023)
Multiple sclerosis (MS) is an autoimmune disease characterized by chronic progressive neurodegeneration of the central nervous system (CNS), and it is the most common inflammatory neurological disease affecting young adults. Given the chronic progressive nature of the disease, psychiatric disorders are more prevalent among these patients, as reported in the literature; however, data in Saudi Arabia are limited. This study aimed to estimate the prevalence of major depression and generalized anxiety disorder in patients with MS and their association with different patient demographics.This was a cross-sectional multicentered study that included adult patients with MS from June 30, 2021, to June 30, 2022. Participants were interviewed in person and asked to complete a survey that included general demographics, Patient Health Questionnaire-9 (PHQ-9), and Generalized Anxiety Disorder-7 (GAD-7) questionnaire. Other variables related to the patients' condition, such as MS type and Expanded Disability Status Scale (EDSS) score, were collected from the patient electronic records. Descriptive statistics were performed, and associations were made using the Chi-square, Fisher's exact, and Analysis Of Variance (ANOVA) tests, as appropriate.A total of 192 participants were included in this study. Based on a cutoff score of >10 on the GAD-7 and PHQ-9 scales, the prevalence of generalized anxiety disorder was 26.1% (n=50), with the majority of participants having minimal anxiety (40%); meanwhile, the prevalence of major depression was 42.7% (n=82), and most of them had mild depression (30%). Female participants scored significantly higher compared to males on the GAD-7 scale (p=0.0376), but not in PHQ-9 scale (p=0.1134). In addition, no statistically significant association was detected between functional disability (EDSS score) and prevalence of anxiety and depression.This study demonstrated a high prevalence of generalized anxiety disorder and major depression among patients with MS compared with that in general population, with females being more affected.